A prospective observation study on diabetic foot ulcer using diabetic ulcer severity score at tertiary care hospital - Saraswat, Bharti; Gill, Kapil Kumar; Yadav, Ashok; Kumar, Krishan (International Surgery Journal, 2021)
Background: A number of scoring systems and classifications are available for diabetic foot ulcers with intention to compare the treatment modalities and future outcomes. Many of them are complex and don’t predict future outcome within the patients. Aim and objectives of current study were to establish a wound-based clinical scoring systems (DUSS) as daily clinical practice by assessing the efficacy of diabetic ulcer severity score. Methods: A total of 73 diabetic patients with foot ulcers were included in this prospective observational study conducted at Dr. S.N. Medical college, Jodhpur and attached hospitals from July 2018 to August 2020. Ulcers were assessed and DUSS score created. Patients were followed up for six months or until healing or amputation if either. Results: In this prospective study of 73 patients with diabetic foot ulcers, most common age group affected was between 51-70 years. Mean age group was 58.57±12.66 years. Mean duration of diabetes was 7.61±5.72 years. Most commonly ulcers were of DUSS score 2. Mean DUSS score was 1.97±1.15. Majority of diabetic foot ulcer patients (37 out of 51) with DUSS score 0, 1 and 2 healed by primary intention after wound debridement. Those with score 3 & 4 majority of them (20 out of 22) had amputation. Conclusions: This is a very simple scoring system that provides an easily accessible and a streamlined approach in the clinical setting without need of any advanced investigative equipment. Hence this can be applied in any set up.